ANALISA PERENCANAAN STRATEGI KORPORASI PT SA AIRLINES DENGAN METODE EVALUASI FAKTOR EXTERNAL (EFE). - Ganis Sanhaji, Ganis Sanhaji; Musyfiq Amrullah, Musyfiq Amrullah; Abdussalam, Abdussalam; Rohmatunnissa, Rohmatunnissa; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Muhajirin, Muhajirin (Media Nusantara, 2023)
PT. SA Airlines is one of the well-known airline companies in the United States. One of the authors conducted research while still studying in the United States. Through this research, the theory and application of Corporate Strategy regarding the development of this large international scale aviation company will be fully explored. Using the External Factor Evaluation method, the corporate strategy of PT SA Airlines will be analyzed. External Factor Evaluation (EFE) is a strategic management tool used to analyze the external environment or macro-environmental factors that can affect an organization. It is part of the broader process of strategic analysis and is particularly useful in the context of strategic planning and competitive analysis. The External Factor Evaluation helps organizations PT. SA to: - Gain a comprehensive understanding of the external environment and its potential impact on business operations.-Identify key opportunities and threats in the external environment. - Compare their performance against competitors or industry standards.- Formulate or adjust strategies to leverage strengths and opportunities and mitigate weaknesses and threats. Overall, the EFE matrix is a valuable tool for strategic planning as it provides a structured approach to assess and respond to external factors influencing organizational performance.